Structural Organization of Murine Intracisternal A Particles - Wivel, Nelson A. (1973)
Isolated murine intracisternal A particles have a distinctive set of structural properties as compared to the recognized oncogenic ribonucleic acid tumor viruses. A particles consist of two closely approximated concentric shells. The outer shell is largely, but not entirely, susceptible to treatment with detergents such as deoxycholate and Triton X-100. The inner shell is resistant to these agents and is stabilized against solubilization by sodium dodecyl sulfate as a result of disulfide bonding between its constituent proteins. The major A particle structural protein (molecular weight approximately 70,000) is contained in the inner shell. A protein component with a molecular weight of about 80,000 may be preferentially concentrated in sites of firm attachment between the inner and outer shells.